Comparing sputum, nasopharyngeal swabs, and combined samples for respiratory bacterial detection using multiplex PCR - Keun Ju Kim; Seung Gyu Yun; Myung-Hyun Nam; Chang Kyu Lee; Yunjung Cho (Microbiology Spectrum)
ABSTRACT Respiratory tract infections are major global health issues that require rapid and accurate diagnostic methods. Multiplex quantitative PCR (qPCR) is commonly used for pathogen detection in respiratory samples. However, the optimal specimen selection for detecting bacterial pathogens is not well-explored. We evaluated the detection rates of respiratory bacteria from nasopharyngeal swabs (NPS), sputum, and combined NPS and sputum samples using multiplex qPCR (Allplex PneumoBacter Assay, Seegene). Paired NPS and sputum samples from 219 patients with acute respiratory symptoms admitted to Korea University Anam Hospital were analyzed. qPCR was performed to detect seven respiratory bacteria: Bordetella parapertussis, Bordetella pertussis, Chlamydophila pneumoniae, Haemophilus influenzae, Legionella pneumophila, Mycoplasma pneumoniae, and Streptococcus pneumoniae. Combined NPS and sputum samples (n = 92) were created from 46 pairs of positive and 46 pairs of negative signals for NPS-alone and sputum-alone samples. Sputum samples (44.3%; 97/219) had a significantly higher positivity rate compared to NPS samples (21.0%; 46/219) (P < 0.001). The 92 combined samples identified a total of 65 bacterial nucleic acids. The detection rate for the combined samples was 86.2% (56/65), which was comparable to that of sputum alone (89.2%; 58/65) and higher than that of NPS samples (50.8%; 33/65). Combining NPS and sputum samples for PCR testing may offer an alternative for bacterial pathogen detection, providing rates comparable to those of sputum alone and greater sensitivity than that of NPS alone. This combined approach could be a cost-effective method to maximize diagnostic yield, reduce the need for multiple tests, and improve the management of respiratory infections.IMPORTANCEThis study offers important insights into refining diagnostic strategies for respiratory bacterial infections using multiplex PCR. This study finds that combining sputum and nasopharyngeal swabs into a single tube could serve as an effective alternative for detecting respiratory bacteria in adults with acute respiratory illness.